2011
DOI: 10.1007/s00586-010-1588-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of adjacent-segment mobility after cervical disc replacement versus fusion: RCT with 1 year’s results

Abstract: Disc prostheses have been designed to restore and maintain cervical segmental motion and reduce the accelerated degeneration of the adjacent level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 46 publications
0
22
0
1
Order By: Relevance
“…However, the quality of motion in terms of COR might not be perfectly maintained or restored and might explain why clinical and radiographic results in terms of adjacent segment degeneration do not differ between CDR and ACDF in selected studies [22]. A mismatch between the physiologic kinematics and that after a CDR implantation might also explain why several studies using QMA did not identify differences regarding adjacent segment motion comparing ACDF and a variety of CDRs used [18,24,28].…”
Section: Discussionmentioning
confidence: 99%
“…However, the quality of motion in terms of COR might not be perfectly maintained or restored and might explain why clinical and radiographic results in terms of adjacent segment degeneration do not differ between CDR and ACDF in selected studies [22]. A mismatch between the physiologic kinematics and that after a CDR implantation might also explain why several studies using QMA did not identify differences regarding adjacent segment motion comparing ACDF and a variety of CDRs used [18,24,28].…”
Section: Discussionmentioning
confidence: 99%
“…However, the findings of these studies are ambiguous: some trials [3, 7-9, 26, 33, 38, 48] suggested better neurologic outcomes and lower incidence of developing adjacent segment degeneration with arthroplasty versus fusion, whereas others [20,[29][30][31] reported no difference between two procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Both anterior cervical decompression and fusion (ACDF) and cervical disc arthroplasty (CDA) have been demonstrated by many level I studies to achieve clinical success, relieve symptoms of neural compression, and improve health-related quality of life. 2 , 4 , 17-19 However, the effect of CDA on reoperation rates has not been observed in all studies, [20][21][22][23][24][25] nor confi rmed in all metaanalyses. 8 -16 Recent investigational device exemption (IDE) studies have demonstrated lower rates of reoperation in patients who undergo CDA than in patients who undergo ACDF.…”
mentioning
confidence: 99%